The Role of Gut Mucins in the Etiology of Depression - Rivet-Noor, Courtney; Gaultier, Alban (Frontiers in Behavioral Neuroscience, 2020)
Major depressive disorders are global health problems that affect more than 6% of the U.S. population. Despite years of research, the etiology of depression remains unclear. Historically, it was believed that depression started within the central nervous system (CNS), but alternative hypotheses have recently challenged this dogma. Indeed, experimental and clinical evidence show that the gut microbiome could be an active player in depression initiation. The composition of bacterial species in depressed patients is significantly different from control microbiomes, and the transfer of the microbiome from depressed patients is sufficient to initiate depressive symptoms in animals. Additionally, the gut microbiome is known to change in the presence of depression risk factors such as chronic stress. While there is strong evidence delineating a role for microbial dysbiosis in depression, the initiating event for this dysbiosis remains unknown. Within the gut, microbiota reside in the mucus layer, a critical gel-like barrier involved in protecting the host from unwanted pathogen interactions, as well as regulating the immune system. Though the mucus layer is often ignored in the face of dysbiosis, it represents a dynamic and important piece of host machinery that has the potential to impact a wide variety of biological processes. Here, we review evidence supporting the novel concept that stress can modify the delicate mucus-microbiome balance, initiating dysbiosis, and ultimately leading to depression.